Doses and intervals of application of potassium phosphite for the control of passion fruit scab - Mauro Ferreira Bonfim; Laine Denez; Míriam Daleffe Innocenti; Henrique Belmonte Petry; Emílio Della Bruna (Revista Brasileira de Fruticultura, 2023)
Abstract Passion fruit scab (PFS), which is caused by species of the fungal complex Cladosporium cladosporioides, occurs both in protected environments and in the field. In view of the importance of the passion fruit scab, this study aimed to evaluate the effect of different intervals and doses of potassium phosphite in the greenhouse and in the field on the incidence of the disease. To evaluate the best dose of potassium phosphite, three experiments were carried out, two in a greenhouse and one in the field. The best application interval was evaluated in another experiment in a greenhouse. The variables evaluated were the incidence of plants with PFS symptoms (%) and the incidence of defoliated plants (%) in all experiments. The harvested fruits were evaluated for their mass (g), diameter (cm), soluble solids, acidity and chlorophyll content. The present work allowed to conclude that the dose of 0.1% of potassium phosphite was the best to control the passion fruit scab in a greenhouse, the treatment with an interval of 28 days of application showed a lower incidence of scab in seedlings at 35 days after inoculation and that potassium phosphite did not interfere in the quality parameters of fruits and leaves of passion fruit evaluated.